2019
DOI: 10.1016/s2468-2667(18)30202-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of London's low emission zone on air quality and children's respiratory health: a sequential annual cross-sectional study

Abstract: SummaryBackgroundLow emission zones (LEZ) are an increasingly common, but unevaluated, intervention aimed at improving urban air quality and public health. We investigated the impact of London's LEZ on air quality and children's respiratory health.MethodsWe did a sequential annual cross-sectional study of 2164 children aged 8–9 years attending primary schools between 2009–10 and 2013–14 in central London, UK, following the introduction of London's LEZ in February, 2008. We examined the association between mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 43 publications
0
58
0
Order By: Relevance
“…A study published in 2009 found no significant cross-sectional association between NO 2 concentrations and respiratory and allergic disorders in adults [39]. Lan et al investigated the effects of NO 2 on children's respiratory health and found that children's lung function indicators, such as forced vital capacity, were inversely correlated with annual NO 2 levels (−0.0023 l/μg per m 3 ; −0.0044 to −0.0002; P = 0.033) [40].…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2009 found no significant cross-sectional association between NO 2 concentrations and respiratory and allergic disorders in adults [39]. Lan et al investigated the effects of NO 2 on children's respiratory health and found that children's lung function indicators, such as forced vital capacity, were inversely correlated with annual NO 2 levels (−0.0023 l/μg per m 3 ; −0.0044 to −0.0002; P = 0.033) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution-related health effects in children include reduced respiratory function [2], asthma [3], obesity [4], and reduced cognition [5]. A study of school children in London found associations of NO 2 exposure with long-term reductions in lung capacity (forced vital capacity [FVC]) [6]. In Australia, decreased lung capacity was measured even in the presence of relatively low levels of ambient NO 2 [7] and, in Southern California, the magnitude of lung damage from NO 2 exposure was roughly equivalent to maternal smoking [8].…”
Section: Introductionmentioning
confidence: 99%
“…those fuelled by diesel, include levies on fuel, surcharges for parking and the introduction of low-emission zones (LEZ). However, whilst large-scale LEZs can deliver improvements in urban air quality, data suggest that, at least in densely populated European cities, more ambitious schemes are required to meet legislative limits and deliver improvements to childhood respiratory health, including asthma symptoms [ 35 ]. The introduction and rigorous evaluation of zones with greater reductions in pollutant concentrations are clearly warranted and may benefit from adjuvant clean air zones that introduce no vehicle idling areas, minimise congestion and support active and low-emission travel through the integration of public transport networks, including park-and-ride schemes.…”
Section: Targets For Actionmentioning
confidence: 99%